Diagnóstico, previsão e tendência da atividade econômica no setor primário brasileiro - Simonassi, Vanessa Gomes (2008)
The impact on the Gross National Product of investiments, interest rates, exchange rates and prices of agricultural exported products are unknown in time to permit previous evaluation of economic activity of Brazilian primary sector. The present work has the objective to preview Brazilian economic activity trend. Econometric techniques are temporal series will be used besides of variables as investiments, interest rates, and trend of national primary sector activity. The present work permits to know changes in production techniques. Also, permits verify a sustainable growth primary sector as indicated by cointegration between products and investiments, showing that investiments of primary sector has been accompanied the production, avoiding, then, eventual saturation and inflationary press on prices of agricultural products.